Systemic sporotrichosis in an alcoholic patient, - Barros,Norami de Moura (2020)
Abstract A 44-year-old male patient presented with nodules that evolved with inflammation, following drainage of seropurulent secretion and ulceration. The patient had a 6 year-history of alcohol addiction and reported contact with cats. At the physical examination, the patient had skin-colored and erythematous nodules, and ulcers covered with thick, blackened crusts on the face, trunk and limbs. A culture of a nodule fluid revealed growth of Sporotrix sp. He also had pulmonary involvement and therefore the disease was classified as systemic sporotrichosis, a rare form that usually affect patients infected with HIV. Chronic alcohol abuse was considered the factor of immunosuppression for the patient.